Central Corneal Thickness in Mentally Challenged (MC) Children - Jethani, Jitendra; Patel, Mital; Shah, Mehul (International Journal of Pediatrics and Child Health, 2014)
Purpose: A case-control study to assess central corneal thickness (CCT) values in mentally challenged (MC) children. Participants and Methods: Children with mental disability were enrolled in the study. Age-matched and healthy control subjects from a similar ethnic background were enrolled in the study. Central corneal thickness was measured by ultrasound pachymetry. Six consecutive measurements were made at the center of the cornea of each eye. Only the right eye of each child in each group was included in the statistical analysis. Results: Twenty-seven children in the MC group (14 boys and 13 girls) and 34 age-matched and healthy control subjects (23 boys and 11girls) were enrolled in the study. The mean age was 9.74 ± 2.697 years (range 7- 17years). The mean age in control group was 10.2 ± 2.185 years (range, 8-17 years). In the MC group, mean CCT value was 505.76 ± 31.23 mm in the right eye. In the control group, mean CCT value was 528.59 ± 30.35 mm in the right eye. CCT value in the MC group was significantly lesser than in the control group for right eye (P =0.006). Conclusions: Mentally challenged (MC) children had a decreased central corneal thickness compared with healthy control subjects. CCT should be kept in mind during measurements of intraocular pressure (IOP) in MC children with because decreased central corneal thickness may give an artificially low intraocular pressure measurement by applanation tonometry.